Venom of the giant ant Dinoponera quadriceps attenuates inflammatory pain in mouse cutaneous wound healing model - Ana Maria Sampaio Assreuy; Beatriz Lima Adjafre; Évilla Rayanne Oliveira Sousa; Ana Paula Negreiros Nunes Alves; Alana de Freitas Pires; Yves Quinet; Mário Rogério Lima Mota (Acta Scientiarum. Biological Sciences, 2020)
Arthropod venoms are potential sources of bioactive substances, providing tools for the validation of popular use and new drugs design. Ants belonging to the genus Dinoponera are used in the folk medicine to treat inflammatory conditions. It was previously demonstrated that the venom of the giant ant Dinoponera quadriceps (DqV), containing a mixture of polypeptides, elicit antinociceptive effect in mice models of chemical, mechanical and thermal nociception. The aim of this study was to evaluate DqV antiinflammatory and antihypernociceptive effects in a mice model of traumatic cutaneous wound. Colonies of D. quadriceps were collected in the ‘‘Serra de Maranguape’’ (State of Ceará, northeastern Brazil), a small mountain range located on the coastal zone, and the venom secreted by the ant glands was extracted with capillary tubes, further lyophilized and maintained at -20 ± 1ºC until use. Wounds were performed in the dorsum of Swiss mice. Animals received intravenous (i.v.) injection of DqV (50 µg -1kg day-1) during 3 days for evaluation of inflammatory parameters present in the wounds: hypernociception, leukocyte infiltrate, myeloperoxidase activity, nitrite nitrate-1 content. Data was tested by two-way ANOVA and Bonferroni’s post-hoc test. DqV reduced (2.7 folds) hypernociception at 48 hours, leukocyte infiltration by 65% at 6 hours and myeloperoxidase activity by 60% at 0.5 hour after wound induction. In conclusion, the venom extracted from D. quadriceps glands attenuates inflammation and hypernociception in mice cutaneous wounds.